2011
DOI: 10.3109/00207454.2011.602808
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin B Receptor Expression in Human Astrocytoma: Association With Clinicopathological Variables and Survival Outcomes

Abstract: The endothelin (ET) axis has been implicated in astrocytoma growth and progression. Selective ETB receptor antagonists blocked proliferation and induced apoptosis in astrocytoma cell lines, suggesting that the ETB receptor could be a therapeutic target for astrocytomas. In the present study, we explored the association of the ETB receptor expression with clinicopathological variables and the prognosis of human astrocytomas, by examining the ETB receptor expression and Ki-67 staining in 71 surgically resected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…To our knowledge, this is the first report to demonstrate that ETBR is an independent prognostic marker for human oesophageal cancer. Previous studies have also demonstrated that tumour ETBR expression was a negative prognostic marker in other cancers (Shen et al , 2011). On the other hand, ETBR gene expression was reported as a positive prognostic marker in renal cell carcinoma (Wuttig et al , 2012).…”
Section: Discussionmentioning
confidence: 82%
“…To our knowledge, this is the first report to demonstrate that ETBR is an independent prognostic marker for human oesophageal cancer. Previous studies have also demonstrated that tumour ETBR expression was a negative prognostic marker in other cancers (Shen et al , 2011). On the other hand, ETBR gene expression was reported as a positive prognostic marker in renal cell carcinoma (Wuttig et al , 2012).…”
Section: Discussionmentioning
confidence: 82%
“…The sections were then counterstained with hematoxylin, dried, and mounted with xylene-based mounting medium. Positive staining was graded as low or high as described [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of ETBR in GBM was associated with a poor prognosis in a Chinese population [ 12 ]. Since ethnicity may play a major role in the pathogenesis of gliomas [ 13 , 14 ], we investigated whether ETBR overexpression could be detected in patients with GBM and in other cancers outside of China, whether ETBR expression correlates with patient survival (and thus its potential use as a prognostic marker and/or therapeutic target), and whether clinically available endothelin receptor blockers/antagonists have toxic effects on cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Of the candidate studies, 13 articles failed to completely describe the available survival data. Finally, 51 published studies in total were included in the analysis after eliminating articles unsatisfying the selection criteria and duplicates (Jaros et al, 1992;Torp et al, 1992;Montine et al, 1994;Ellison et al, 1995;Heegaard et al, 1995;Kros et al, 1996;Coons et al, 1997;Pollack et al, 1997;Dehghani et al, 1998;McKeever et al, 1998;Ritter et al, 1998;Figarella-Branger et al, 2000;Rodriguez-Pereira et al, 2000;Ho et al, 2001;ReaveyCantwell et al, 2001;Zhong et al, 2001;Bredel et al, 2002;Pollack et al, 2002;Bowers, 2003;Chiang et al, 2003;Neder et al, 2003;Wessels et al, 2003;Zamecnik et al, 2003;Preusser et al, 2005;Uematsu et al, 2005;Kleinschmidt-DeMasters et al, 2006;Donato et al, 2007;Kanamori et al, 2008;Kuo et al, 2009;Laks et al, 2009;Li et al, 2009;Armstrong et al, 2010;Nabika et al, 2010;Watanabe et al, 2010;Yoshida et al, 2010;Habberstad et al, 2011;Margraf et al, 2011;Qiang et al, 2011;Shen et al, 2011;Zawrocki et al, 2011;…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%